Effect of crude polyphenol extracted from black olive fruit (olea europae) on some physiological and immunological parameters in Males Rats Treated with Hydrogen Peroxide: Luma W. Khalil, Layla Hashim Alol and Anwar I. Obead - Khalil, Luma W. (The Iraqi Journal of Veterinary Medicine, 2013)
The present study was designed to demonstrate the effect of crude alcoholic extract of polyphenol in olive (200 mg/kg) on some physiological and immunological parameters in male rats treated with 1% hydrogen peroxide (H2O2). Twenty rats were divided randomly into four equal groups and treated for (30) days as follows: control group (c) which were given ordinary tap water, first treated group (G1) was given 1% H2O2 in drinking water, the second treated group (G2) was given alcoholic extract of polyphenol in olive (200 mg/kg) by oral intubation, third treated group(G3) was given H2O2 and polyphenol. Blood samples were collected after 30 days for measuring the following parameters: Total WBC count, the percentage of WBC differential count (%) ,platelet count ,serum protein ,albumin and globulin , Neutrophil /lymphocyte index, Albumin /Globulin and Phagocytic index. The results showed a significant increase in, total WBC count of polyphenol treated group (G2) and polyphenol compounds plus H2O2, Lymphocyte percentage in both polyphenol (G2) and polyphenol with H2O2 (G3) treated groups ,percentage of neutrophil in H2O2 (G1) group and monocyte percentage in both H2O2 (G1) and H2O2 with polyphenol (G3) groups as compared with control group. Significant depression in platelet count in H2O2 group (G1) as compared with other treated groups was also recorded. The immunological test showed a significant increase in phagocytic index in polyphenol and H2O2 group (G3) as compared with other groups. The result also pointed a significant increase in the concentration of protein and globulin in polyphenol compounds with H2O2 group (G3) and also a significant increase in albumin concentration of group G2, while there was a significant decrease in globulin concentration of H2O2 (G1) group as compared with other groups. On conclusion it seems that treatment with alcoholic extract of polyphenol in olive at concentration of 200 mg/kg B.W. has the ability to correct the adverse effect of hydrogen peroxide in male rats.